Causal Factors which influence Islamic Cooperative Performance in Thailand - Sulong, Mazlan; Laeheem, Kasetchai (NIDA Development Journal, 2018)
The Objective of this research was to study the causal factors which influence Islamic Cooperative Performance in Thailand. The research is a survey research coverers the sample of 376 Islamic Cooperative administrators saluted tie rough stratifies sampling. Data were gathered by questionnaire and analyzed by using Structural Equation Modeling (SEM) The results indicated that adjusted model fitted well with the empirical data. (Relative Chi-Square (χ2/df) = 2.04, Goodness of Fit Index (GFI) = 0.94 and Root Mean Squared Error of Approximation (RMSEA) = 0.05) analyzing the causal factors affecting the cooperative management in terms of direct effect by personnel readiness followed by shared values and strategic orientation. Finally, causal factors affecting the cooperative performance in terms of direct effect by personnel readiness followed by strategic orientation and cooperative management.